EVALUASI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN AKIDAH AKHLAK (PAI) DI SMP NEGERI 41 PALEMBANG PROVINSI SUMATERA SELATAN - Badariah; Ade Imelda Firmayanti; Endang Ekowati (UNISAN JURNAL, 2022)
Education in a philosophical perspective is an effort to help humanize humans. This means that humans will become real humans when they are given education. Or in other words, there are humans who do not become old because they do not get an education. Islamic education views that education is a conscious guidance or leadership by the educator towards the physical and spiritual development of the educated towards the formation of the main personality. At the axiological level, education is an important means to obtain quality human resources (HR) to ensure the survival and progress of a nation. The lack of quality human data sources (HR) is strongly influenced by the development of education in the world, including Indonesia today.In Indonesia, increasing human resources through improving education is a very urgent matter to be realized immediately to be able to face the global era. Education is a conscious and planned effort in order to create a learning atmosphere and learning process so that students actively develop the potential that exists in themselves to be able to have religious spiritual strength, self-control, personality, intelligence, noble character and various skills needed for themselves, society, nation. and country.In learning, evaluation activities are used for the benefit of improving the learning process itself, besides that it aims to assess or assess the growth and progress of students towards the goals or values that have been set by the educational program itself. The evaluation approach in an effort to determine the effectiveness of learning at SMP Negeri 41 Palembang, South Sumatra Province uses an evaluation approach that can cover the entire education process. This means that all components related to the learning process are things that need to be studied and investigated in real terms. Keywords: evaluation, quality, faith and morals